THE EFFECTIVENESS OF HEALTH EDUCATION USING VIDEO MEDIA ON KNOWLEDGE OF PULMONARY TB PREVENTION IN NURSING STUDENT IN WAMENA - Sethiana Dewi Ruben; Ellen Rosawita Veronica Purba Veronica Purba; Elisabeth Gultom (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Indonesia is the fifth country in Southeast Asia with the most cases of pulmonary TB. Papua is one of the provinces with a high incidence of pulmonary TB. One of the efforts to reduce the number of pulmonary TB is providing health education about tuberculosis prevention efforts using audiovisual media. This study aims to determine the effectiveness of health education using video media on knowledge of pulmonary TB prevention. The research used the design of The One Group Pre Test – Post Test, with the type of research being Quasi Experiment. It was carried out in the Wamena Nursing DIII Study Program with a sample of 32 respondents. Respondents were given a pre-test questionnaire and a health education intervention using video. After ten days of providing health education, respondents were given a questionnaire (post-test). Statistical analysis using Wilcoxon. The results showed a significant increase in knowledge about pulmonary TB prevention between the pre-test and post-test (p=0.000). It was concluded that health education using audiovisual media was more effective in providing information on the prevention of pulmonary TB.